Development of Embodied Word Meanings: Sensorimotor Effects in Children’s Lexical Processing - Inkster, Michelle; Wellsby, Michele; Lloyd, Ellen; Pexman, Penny M. (Frontiers in Psychology, 2016)
Previous research showed an effect of words’ rated body-object interaction (BOI) in children’s visual word naming performance, but only in children 8 years of age or older (Wellsby & Pexman, 2014a). In that study, however, BOI was established using adult ratings. Here we collected ratings from a group of parents for children’s body-object interaction experience (child-BOI). We examined effects of words’ child-BOI and also words’ imageability on children’s responses in an auditory word naming task, which is suited to the lexical processing skills of younger children. We tested a group of 54 children aged 6-7 years and a comparison group of 25 adults. Results showed significant effects of both imageability and child-BOI on children’s auditory naming latencies. These results provide evidence that children younger than 8 years of age have richer semantic representations for high imageability and high child-BOI words, consistent with an embodied account of word meaning.